Rheumatoid Factor Positivity is Associated with Lower Bone Mass in Korean Male Health Examinees without Clinically Apparent Arthritis - Hwang, Jiwon; Ahn, Joong Kyong; Lee, Jaejoon; Koh, Eun-Mi; Cha, Hoon-Suk (Journal of rheumatic diseases, 2019)
Objective. This cross-sectional study aimed to investigate the association between rheumatoid factor (RF) positivity and bone mineral density (BMD) in male Korean subjects without any history of joint disease. Methods. Of 84,344 males who had undergone a comprehensive health checkup program in 2012, 1,390 male health examinees were recruited, whose BMD and RF results were available. A RF titer ≥20 IU/mL was considered positive. BMD was measured at lumbar spine (L1∼L4) or hip (femoral neck and total hip) by dual-energy X-ray absorptiometry. Results. The association between RF positivity and BMD was assessed by multiple linear regression analysis. The mean age was 52.7±10.9 years (range 19∼88 years), and RF was detected in 64 subjects (4.6%). Demographics and laboratory data were not different between RF-positive and -negative subjects except hepatitis B surface antigen (HBsAg), which was more frequently seen in RF-positive subjects (15.6% vs. 4.3%, p=0.001). RF-positive subjects had significantly lower BMD compared to RF-negative subjects in lumbar spine but not in total hip regardless of the existence of HBsAg (1.17±0.16 g/cm2 vs. 1.10±0.18 g/cm2, p=0.002 in total subjects; 1.17±0.16 g/cm2 vs. 1.10±0.18 g/cm2, p=0.004 in HBsAg-negative subjects). After adjusting for multiple confounders, RF positivity was negatively associated with lumbar spine BMD (B=−0.088 and standard error=0.035, p=0.011). Conclusion. Our results show that the presence of RF could have an unfavorable impact on bone density in apparently normal males. Additional studies to elucidate the osteoimmunological mechanism of rheumatoid factor are warranted. KCI Citation Count: 0